2020
DOI: 10.1016/j.system.2019.102186
|View full text |Cite
|
Sign up to set email alerts
|

The suitability of film for modelling the pragmatics of interaction: Exploring authenticity

Abstract: Previous studies have highlighted the potential of film to promote the development of L2 pragmatics by presenting to learners the types of authentic, contextually-appropriate language use routinely absent from textbooks. However, the issue of authenticity is multifaceted and there has been little if any exploration of authenticity in terms of larger sequences within scripted texts. Sequence authenticity is particularly relevant to learners, as it demonstrates how actions are achieved over multiple turns, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Instead, they argue scripted and planned elements are used to reflect conversations (e.g. Kozloff 2000;Ryan & Granville 2020). Nevertheless, and in agreement with Kaiser & Shibahara (2014: 1), this material constitutes "a window into the world of the target language and culture," and it represents a more useful source than textbooks to describe the context of meaning.…”
Section: Audiovisual Inputmentioning
confidence: 93%
“…Instead, they argue scripted and planned elements are used to reflect conversations (e.g. Kozloff 2000;Ryan & Granville 2020). Nevertheless, and in agreement with Kaiser & Shibahara (2014: 1), this material constitutes "a window into the world of the target language and culture," and it represents a more useful source than textbooks to describe the context of meaning.…”
Section: Audiovisual Inputmentioning
confidence: 93%
“…Indeed, several researchers have argued that film-based dialogues fail to reflect the pragmatics of ordinary speech (Kozloff, 2000;Cohen, 2008;Rossi, 2011;Toolan, 2011). Particularly, in the recent study conducted by Ryan and Granville (2020), which aimed at examining invitation sequences and the openings and closings of phone calls in films and in daily life, the authors reported a clear mismatch between the pragmatics of film dialogues and ordinary conversations. After a rigorous conversational analysis of turn-by-turn progression sequences, findings revealed that some aspects of the "sequencing of talk" are not represented in film dialogues, suggesting that films may reflect inaccurate models of conversations (Ryan & Granville, 2020, p. 11).…”
Section: Ii4 Using Films To Raise (Meta)pragmatic Awarenessmentioning
confidence: 99%
“…Indeed, several researchers have argued that film-based dialogues fail to reflect the pragmatics of ordinary speech Cohen, 2008;Rossi, 2011;Toolan, 2011). Particularly, in the recent study conducted by Ryan and Granville (2020), which aimed at examining invitation sequences and the openings and closings of phone calls in films and in daily life, the authors reported a clear mismatch between the pragmatics of film dialogues and ordinary conversations. After a rigorous conversational analysis of turn-by-turn progression sequences, findings revealed that some aspects of the "sequencing of talk" are not represented in film dialogues, suggesting that films may reflect inaccurate models of conversations (Ryan & Granville, 2020, p. 11).…”
Section: Ii4 Using Films To Raise (Meta)pragmatic Awarenessmentioning
confidence: 99%